2011
DOI: 10.1186/1752-1947-5-314
|View full text |Cite
|
Sign up to set email alerts
|

Unusual association of ST-T abnormalities, myocarditis and cardiomyopathy with H1N1 influenza in pregnancy: two case reports and review of the literature

Abstract: IntroductionMyocarditis is rarely reported as an extra-pulmonary manifestation of influenza while pregnancy is a rare cause of cardiomyopathy. Pregnancy was identified as a major risk factor for increased mortality and morbidity due to H1N1 influenza in the pandemic of 2009 to 2010. However, to the best of our knowledge there are no previous reports in the literature linking H1N1 with myocarditis in pregnancy.Case presentationWe report the cases of two pregnant Caucasian women (aged 29 and 30), with no pre-exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The number of female patients was larger than the number of male patients, although general acute myocarditis is more common in males [69, 70]. Further, although pregnancy is reported to be a risk factor for deterioration of pandemic influenza infection, only one of the women in this paper was pregnant [38]. The mean interval from influenza onset to cardiac involvement was 5.4 days.…”
Section: Myocarditis Associated With Influenza  H1n1pdm2009 In Thementioning
confidence: 96%
“…The number of female patients was larger than the number of male patients, although general acute myocarditis is more common in males [69, 70]. Further, although pregnancy is reported to be a risk factor for deterioration of pandemic influenza infection, only one of the women in this paper was pregnant [38]. The mean interval from influenza onset to cardiac involvement was 5.4 days.…”
Section: Myocarditis Associated With Influenza  H1n1pdm2009 In Thementioning
confidence: 96%
“…Extra-respiratory tract complications are occasionally described in pregnant women. These include the development of myocarditis after infection with A(H1N1)pdm09 [28,29], and the development of an encephalopathy associated with a seasonal H3N2 IAV infection from which viral RNAwas detected in cerebrospinal fluids [30].…”
Section: Influenza a Virus Pathogenesis In Pregnant Womenmentioning
confidence: 99%
“…There have been few reports on acute myocarditis during pregnancy, and no consensus exists on delivery strategies after 34 weeks of gestation. Some studies have described abortion [5], whereas some have also reported cases in which the mothers and their children were saved by cesarean section [6]. Both cases with abortion and successful saving of mother and child were reported.…”
Section: Discussionmentioning
confidence: 99%